Analysis of Chemical Characteristic of Casava Flour from Klenteng and Casessart (UJ5) Varieties - Novitasari, Erliana; Arief, Ratna Wylis (Jurnal Penelitian Pertanian Terapan, 2018)
The technology of cassava flour modification has been researched and developed. Biological change by using BIMO-CF containing lactic acid bacteria is a practical technology that is easy to apply in the production of cassava flour. This research was conducted from May until August 2017 at Agrosains Park Natar with the aim to know the chemical characteristics of cassava flour from Klenteng and Casessart varieties. Observation parameters included analysis of moisture content, ash content, fat content, protein content, fiber content, total carbohydrate content, starch content, HCN content, and white degree at THP Polytechnic State Laboratory of Lampung. The results showed that the highest yield was produced by cassava flour from casessart variety with the addition of BIMO-CF were 23.11%. The water content of cassava flour produced ranged between 8.02-9.19%, by the quality requirements of SNI. The lowest ash content was cassava flour from casessart variety (1.19%) without the addition of starter. The addition of starter increased the protein content of cassava flour both of Klenteng variety (0.47%) and Casessart variety (1.11%), decreasing the fiber content for Klenteng variety (0.67%) and Casessart variety (0.90%). The amount of fat contained in cassava flour produced ranged from 0.69 to 0.87%. Carbohydrate content (Klenteng variety was 88.49%, and Casessart variety was 87,69%) and starch content (Klenteng variety was 85,98%, and Casessart variety was 84,83%), cassava flour with the addition of starter higher than cassava flour without the addition of starter. All of the cassava flour produced has HCN levels below the maximum limit (0.0216-0.0293%), while the degree of white (> 80%) has not met the quality requirements of SNI.